Leptin, the Creation of Obesity Gene and its task in Pregnancy - Ishrat, Shakeela; Hussain, Md Zahid; Jahan, Sultana (Journal of Bangladesh Society of Physiologist, 2009)
Leptin is a protein encoded by the âob' gene. Leptin is primarily produced by adipocytes and its primary physiologic function is to suppress body fat. Obese individuals have high serum leptin levels and obesity is a leptin resistant state. There are evidences that leptin levels are higher in pregnant women compared to non pregnant women. Leptin levels increase as pregnancy advances and at term, approximate those found in obese adults. There is speculation that leptin is synthesized in placenta in addition to adipose tissue mass. Leptin may have a permissive, indirect role in regulation of fetal growth. Key Words: Leptin, Adipose tissue, Placenta, Fetus, Growth Â doi: 10.3329/jbsp.v3i0.1803 Â J Bangladesh Soc Physiol.2008 Dec;(3):79-84.